Clinical evaluation of a new monofocal IOL with enhanced intermediate function in patients with cataract - Auffarth, Gerd U.; Gerl, Matthias; Tsai, Linda; Janakiraman, D. Priya; Jackson, Beth; Alarcon, Aixa; Dick, H. Burkhard (Journal of cataract and refractive surgery, 2021)
Purpose: - To evaluate the effectiveness and safety of 2 enhanced monofocal intraocular lenses (IOLs). The TECNIS Eyhance IOL (Model ICB00) was compared with a standard monofocal IOL (TECNIS Monofocal, Model ZCB00). - Setting: - European multicenter study. - Design: - Prospective, bilateral, randomized, comparative/evaluator-masked, controlled study. - Methods: - Adult subjects scheduled to undergo bilateral, primary phacoemulsification cataract extraction and posterior IOL implantation were randomized to receive the enhanced monofocal ICB00 IOL or the monofocal ZCB00 IOL in both eyes. Monocular endpoints at 6 months included distance-corrected intermediate visual acuity (DCIVA), photopic corrected distance visual acuity, and uncorrected intermediate visual acuity (UIVA). Binocular visual acuities, monocular corrected distance contrast sensitivity (first eyes), patient-reported outcomes, and safety were assessed at 6 months. - Results: - Overall, 139 patients were bilaterally implanted with the enhanced monofocal IOL (n = 67) or standard monofocal IOL (n = 72) and available for the 6-month visit. The enhanced monofocal IOL significantly improved mean monocular and binocular DCIVA and UIVA by at least 1-line logarithm of the minimum angle of resolution vs the standard monofocal IOL (all P ≤ .0001). Distance vision for the enhanced monofocal IOL was 20/20 or better and comparable with that of the standard monofocal lens at 6 months. Contrast sensitivity, photic phenomena outcomes, and rates of adverse events were similar between the 2 groups. - Conclusions: - In patients undergoing cataract surgery, TECNIS Eyhance IOL Model ICB00 provided enhanced intermediate vision and similar distance performance and photic phenomena compared with a standard monofocal IOL, along with improved functional performance in daily life.
Gesehen am 08.04.2021